DREADD agonist compound 21 causes acute diuresis in wild-type mice - MacIver, Bryce; Wu, Ali; Hill, Warren G.; Yu, Weiqun (Frontiers in Pharmacology, 2024)
Targeted activation or inhibition of specific cell populations using chemogenetics allows precise dissection of cellular signaling and function. Designer Receptors Exclusively Activated by Designer Drugs (DREADD) is a chemogenetic platform initially developed by mutating human muscarinic receptors to be unresponsive to endogenous acetylcholine but exclusively activated by an "inert" designer drug. Compound 21 (C21) is a new and potent DREADD agonist, however, radioligand assays from a recent report indicated its ability to bind endogenous G protein-coupled receptors (GPCRs) including muscarinic M1-3 receptors. Whether this binding causes off-target effects is unclear. Renal innervation is important for the regulation of renal function, and the advent of chemogenetic tools provides significant opportunities for mechanistic understanding of renal innervation and function. GPCRs such as adrenergic and muscarinic receptors play a role in renal function, thus a careful pharmacological characterization of C21 in renal function is a prerequisite for this approach. Unexpectedly, an infusion of 1.0 mg/kg C21 in anesthetized mice caused a ~ 4-fold increase in urine output and correspondingly increased glomerular filtration rate (GFR), suggesting a C21-mediated acute diuretic effect. This acute diuresis effect was further confirmed in awake mice using voiding spot assays. The exact molecular mechanism for C21-mediated diuresis is unclear, however, we have demonstrated by in vitro myography that C21 can effectively inhibit bladder smooth muscle contraction by antagonizing M3 receptors at the micromolar level, causing increased voiding size in vivo. In summary, C21 functions as a GPCR antagonist and has significant dose-dependent off-target effects in the renal system.